Production of high-quality electron beams in numerical experiments of laser wakefield acceleration with longitudinal wave breaking - P. Tomassini; M. Galimberti; A. Giulietti; D. Giulietti; L. A. Gizzi; L. Labate; F. Pegoraro (Physical Review Special Topics. Accelerators and Beams, 2003)
In 1998 Bulanov et al. [Phys. Rev. E 58, R5257 (1998)] proposed a novel scheme for the production of high-quality electron beams in laser wakefield acceleration in which a controlled longitudinal nonlinear wave breaking is induced by a tailored electron density profile. This proposal was supported by both analytical and numerical results in a spatially one-dimensional configuration. In this paper we present results of a particle-in-cell simulation, two-dimensional in space and three-dimensional in the fields, of the interaction of an ultraintense laser pulse with a preformed plasma where the electron density decreases steeply from a first to a second plateau. We show that in our regime two-dimensional effects play a relevant role, allowing the production of well collimated, short and almost monochromatic electron beam. Remarkably low values of transverse and longitudinal normalized beam emittance ϵ_{rms}^{tr}=9×10^{-2}   mm mrad and ϵ_{rms}^{lon}=2   mm keV are obtained.